New Estrone Oxime Derivatives: Synthesis, Cytotoxic Evaluation and Docking Studies - Catarina Canário; Mariana Matias; Vanessa Brito; Adriana O. Santos; Amílcar Falcão; Samuel Silvestre; Gilberto Alves (Molecules, 2021)
The interest in the introduction of the oxime group in molecules aiming to improve their biological effects is increasing. This work aimed to develop new steroidal oximes of the estrane series with potential antitumor interest. For this, several oximes were synthesized by reaction of hydroxylamine with the 17-ketone of estrone derivatives. Then, their cytotoxicity was evaluated in six cell lines. An estrogenicity assay, a cell cycle distribution analysis and a fluorescence microscopy study with Hoechst 3358 staining were performed with the most promising compound. In addition, molecular docking studies against estrogen receptor α, steroid sulfatase, 17β-hydroxysteroid dehydrogenase type 1 and β-tubulin were also accomplished. The 2-nitroestrone oxime showed higher cytotoxicity than the parent compound on MCF-7 cancer cells. Furthermore, the oximes bearing halogen groups in A-ring evidenced selectivity for HepaRG cells. Remarkably, the Δ9,11-estrone oxime was the most cytotoxic and arrested LNCaP cells in the G2/M phase. Fluorescence microscopy studies showed the presence of condensed DNA typical of prophase and condensed and fragmented nuclei characteristic of apoptosis. However, this oxime promoted the proliferation of T47-D cells. Interestingly, molecular docking studies estimated a strong interaction between Δ9,11-estrone oxime and estrogen receptor α and β-tubulin, which may account for the described effects.